Pengaruh Kualitas Laporan Keuangan Terhadap Efisiensi Investasi - Putra, Gede Diatmika; Damayanthi, I Gst Ayu Eka (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p02, 2019)
The aim of this research is to determine how the quality of financial reports on  underinvestment and overinvestment conditions are affected. The research was  conducted on mining companies listed in the Indonesian Stock Exchange in 2017. The  number of samples on this research is 38 companies. The method of data collection used  is non-technical sampling method with purposisive sampling. The analysis of the data  analysis used is descriptive statistical analysis, model feasibility, multi-logistics  regression analysis, and Walid statistics test. The analysis found that the quality of  financial reports is negative in underinvestment and overinvestment conditions. The  company's high quality financial report would result in a decrease in company probants  that experienced underinvestment conditions compared to the company's probability in  normal investment conditions. The quality of good financial reports can improve  monitoring function for shareholders in monitoring investment decisions made by  managers to avoid overinvestment conditions. Keywords:  Investment efficiency, unverinvestment, overinvestment, the quality of  financial report.